EDUKASI KEGAWATDARURATAN KESEHATAN GIGI DAN MULUT TERHADAP PENGETAHUAN ATLET TAEKWONDO DELTA CLUB - indah, fatimah; Nurwanti, Widi; nurrochman, aditya (AKG Puskesad, 2023)
Background: Napitupulu's research (2019), shows that in the age group 18-24 years identified as having Angle Occlusion Class 1 with symptoms in the form of clicking (72.7%), joint pain (39.4%), muscle pain (39.4%) consisting of from temporalis muscle (6.1%), limited mouth opening (24.2%), and headache (6.1%), orthodontic treatment (27.3%), bruxism (27%). Objectives: Knowing the effect of emergency dental and oral health education on the knowledge of Taekwondo Athletes. Methods: The research design used was experimental with a quasy experimental design with pre and post test designs. The sample in this study were Taekwondo athletes as many as 35 researchers who were taken with a quasi-experimental design. Data analysis in this study used univariate and bivariate tests using the Shapiro-Wilk and Wilcoxon tests. Results: The statistical test shows that there is a difference between the results of the Pre Test and Post Test scores of the respondents' behavior, where the Asymp value. Sig (2-tailed) knowledge variable is 0.000 which means that the variable is <0.05, then it can be said that Ha is accepted. Conclusion: the effect of education on emergency dental and oral health on the knowledge of Taekwondo Athletes.